2023
DOI: 10.1590/s0102-0536-2023-e2506
|View full text |Cite
|
Sign up to set email alerts
|

Chemical desiccants for anticipation of harvest and quality improvement of chickpea seeds

Abstract: Desiccating herbicides can promote uniformity of maturation, and early harvest and provide improvements in the physical, physiological, and sanitary seeds quality. The objective of this work was to evaluate the use of herbicides in early harvest and in the physiological quality of chickpea seeds. The experimental design was of randomized blocks with four replications, considering a complete factorial design with one control (no application) + two factors (four herbicides x three different doses): glufosinate-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Known studies have investigated seed yield, color, physiological quality, legume germination variables, and application of desiccants. , Chamma et al found that the application of desiccants for the forced maturation of soybeans influenced the acquisition of vigor and longevity of the seeds. For chickpeas, Almeida et al observed that using glufosinate (400 g i.a/ha) anticipated harvest by 17 days and increased germination and vigor in chickpea seeds. Although cowpea is widely cultivated in the Brazilian agricultural scenario, the use of herbicides in the preharvest is widespread, and there are still no studies that portray physiological and biochemical parameters that confer quality to seeds obtained from plants desiccated with herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…Known studies have investigated seed yield, color, physiological quality, legume germination variables, and application of desiccants. , Chamma et al found that the application of desiccants for the forced maturation of soybeans influenced the acquisition of vigor and longevity of the seeds. For chickpeas, Almeida et al observed that using glufosinate (400 g i.a/ha) anticipated harvest by 17 days and increased germination and vigor in chickpea seeds. Although cowpea is widely cultivated in the Brazilian agricultural scenario, the use of herbicides in the preharvest is widespread, and there are still no studies that portray physiological and biochemical parameters that confer quality to seeds obtained from plants desiccated with herbicides.…”
Section: Introductionmentioning
confidence: 99%